A Rare Case of Intussusception Associated with Metastasize Small Cell Carcinoma of Lung - Razman Jarmin; Azlanuddin Azman; Nik Ritza Kosai; Srijit Das; Razrim Rahim (Tehran University of Medical Sciences, 2024)
Volume: 50, No: 11